The serotonin transporter 5-HTTPR polymorphism is associated with current and lifetime depression in persons with chronic psychotic disorders - Contreras Rojas, Javier (2009)
artículo (arbitrado) -- Universidad de Costa Rica, Centro de Investigaciones en Biología Celular y Molecular. 2008